Digital Transformation in MSMEs through the Integration of E-Wallets and Social Media Marketing - Ade Rasinta Herli Kristiani Purba (International Forum of Researchers and Lecturers, 2025)
Digital transformation has become a critical factor in enhancing the competitiveness and sustainability of micro, small, and medium enterprises (MSMEs) in the digital economy era. This study aims to examine the integration of e-wallet services and social media marketing strategies as components of digital transformation within MSMEs. Employing a Systematic Literature Review (SLR) approach, the study analyzes 25 relevant scholarly articles published between 2018 and 2025. The findings indicate that the adoption of e-wallets facilitates financial transactions, improves operational efficiency, and promotes compliance with formal financial systems. Meanwhile, the use of social media proves effective in expanding market reach and strengthening customer engagement. However, the adoption of these digital tools remains constrained by several challenges, including limited digital infrastructure, low levels of technological literacy, and resistance to change. These findings offer important implications for policymakers and business practitioners in designing inclusive and sustainable digitalization strategies for MSMEs